Ways of optimizing the methodological support of investigation of illegal participation of officers in business activities - Khlus, A.M. (Bulletin of the Karaganda University “Law Series”, 2021)
The article deals with the problems of a private methodology for investigating illegal participation in entre-preneurial activity. The methodology for investigating this crime, formed on the basis of its forensic charac-teristics, does not contain information about the material components of the structure of this crime. According to the author, the construction of a methodology for investigating the crime in question should be based on in-formation about the elements of its material structure. Having analyzed the criminal-legal signs of the compo-sition of illegal participation in entrepreneurial activity, guided by Art. 429 of the Criminal Code of the Re-public of Belarus and Art. 364 of the Criminal Code of the Republic of Kazakhstan, the author highlighted the elements of its material structure. The material structure of illegal participation in entrepreneurial activity, according to the author, consists of the following elements: the subject of the crime (an official, a person au-thorized to perform public functions, or a person equivalent to him, as well as a person holding a responsible public position); the object of criminal encroachment (state bodies or state or other organizations in which the subject of the crime (official, etc.) carries out his official and other activities; the means of committing a crime (in most cases, these are documents) and the subject of the crime (money or other material values), re-ceived by the subject as a result of the crime, the selection and analysis of the elements of the criminal struc-ture will serve as a theoretical basis, both for building an information model of the act, and for improving the methodological support for the disclosure and investigation of this type of crime.